Chapter 2 Healthcare and technology The multi-level perspective: theories, models, and frameworks - Wouters, Eveline J.M (Taylor & Francis, 2022)
Theories on technology adoption in the context of healthcare for older people have developed from a merely individual usability approach to a richer understanding of deeper personal motivations and values as well as a broader awareness of stakeholders and organisations. The aim of this chapter is twofold: first, to give an overview of the existing frameworks, models and theories that describe the multiple factors at several levels that influence technology uptake in the context of healthcare. Second, to critically analyse the meaning these frameworks, models and theories bring to the human aspects of healthcare technology adoption and use. Because the book focuses on care for older persons, specific attention is given to personal aspects that influence technology acceptance by older people.